Implementasi Model Pembelajaran Examples Non Examples untuk Meningkatkan Hasil Belajar Siswa di SMP Negeri 1 Sindang Kabupaten Indramayu - Surahmi Surahmi (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2023)
This study aims to implement examples non examples learning on the material of excellence and limitations between spaces and the role of economic actors. The subjects of the study were grade VIII.A students at SMP Negeri 1 Sindang, Indramayu Regency. This study used an action research method that was carried out in two cycles. Data is collected through observation, documentation, and tests. Data analysis techniques use qualitative descriptive methods. The results showed that learning examples non examples can improve student learning outcomes with an average score of 81.71 in cycle II. The examples non examples learning model also increases students' critical power to analyze, describe, and conclude something contained in the examples given to learn and master the concepts of the material being presented.